Introduction to inductively coupled plasma atomic emission spectroscopy. - Moore, G. L. (Glyn Llewellyn), 1940- (Analytical spectroscopy library, 1989)
Today, atomic emission spectroscopy is a well-established analytical technique of widespread application - a technique that no-one involved or interested in chemical analysis can afford to ignore. The present book was written to meet the need for an extensive introduction to this technique. It is written in an easy-to-understand way, and is mainly aimed at tertiary-level students at universities and colleges, and at newcomers to the field. The book prepares the reader for the study of more advanced texts and the increasing number of research papers published in this area. It will not only be of great use to the analytical chemist, but will appeal to specialists in other fields of chemistry who need an understanding of analytical techniques. The book introduces the analytical techniques of atomic emission spectroscopy, outlining the principles, history and applications. It discusses spectrography, excitation sources, inductively coupled plasmas, instrumentation, nebulization, sample dissolution and introduction, accuracy and precision, internal standardization, plasma optimization, line selection and interferences, and inductively coupled plasma mass spectroscopy. Understanding of the material is aided by 128 illustrations, including 11 photographs. References follow each chapter, and an extensive index completes this useful work.